Spindle cell oncocytoma of adenohypophysis: Review of literature and report of another recurrent case. Issue 6 (19th June 2017) - Sali, Akash; Epari, Sridhar; Tampi, Chandralekha; Goel, Atul
Abstract : Spindle cell oncocytoma (SCO) of adenohypophysis was first described in 2002 by Roncaroli et al. as a new entity in the tumors originating from adenohypophysis. It was subsequently recognized as a distinct entity in the 2007 WHO classification of CNS tumors and retained in the current updated classification. In contrast to that suggested by the original authors, this tumor does have a potential for recurrence as first described by Kloub et al. and later with many such case reports. This tumor can be confused with other sellar tumors like pituicytomas and pituitary adenoma, both radiologically and histopathologically. However, it is imperative to differentiate these tumors from the above‐mentioned differential diagnoses as it certainly has a recurrent potential. To date only 34 cases of SCO have been published in the English literature. Herein we present a rare SCO case with unusually aggressive course in a 64‐year‐old man, which recurred 4 years after the initial diagnosis.